CFD Prediction and Experimental Measurement of Blade Water Coverage in a Diesel Turbocharger. (12th September 2012) - Yao, Jun; Yao, Yufeng
Abstract : A turbocharger unit for diesel engine is often equipped with a built-in online water washing system and its performance is not always satisfactory because of efficiency declination due to deposit accumulated on blade surfaces not being washed away. In this study, a systematic approach of using experimental measurements and computational fluid dynamics (CFD) is adopted to analyse liquid/gas two-phase flow associated with a turbocharger water washing system, in order to understand the underlying flow physics. A medium-sized diesel engine turbocharger configuration is chosen for this purpose. Experiments are focussed on blade surface temperature measurements, while CFD modelling with a coupled Eulerian/Lagrangian method is used for capturing the complex gas/liquid two-phase flow behaviours inside the induction duct and the blade passage. It was found that numerical predictions are in a good agreement with experimental data in terms of temperature distributions of the blade leading edge region and water coverage over the blade ring. Other flow features such as the water droplet trajectories and the particle size distributions are also explored and analysed in further details, and they are useful for understanding the deposit removal mechanism.